(untitled) (Journal of EAHIL, 2024)
The integration of ChatGPT into library promotions has transformed promotional efforts for the library team at King’s. With its adaptability, ChatGPT enables the creation of personalised, dynamic email content tailored to specific interests swiftly. This not only enhances promotional effectiveness but also saves considerable time, allowing the team to focus on other services like literature search support. Consistently, ChatGPT has increased attendance and service uptake, showcasing its potential to enrich promotional activities, amplify impact, and strengthen connections with patrons. This technological advancement is instrumental in advancing the role of library professionals in the digital age, demonstrating the profound impact of AI integration in library services.